Distopias audiovisuais: experiências mentais em circulação - Bocca, Jean Pierre (Universidade do Vale do Rio dos Sinos, 2021)
In the face of complexification of social processes, the exacerbation of individuality, intolerance and incivility, a conservative and extremist tendency, harmful and destructive behaviors, and the challenges imposed by climate change, individuals are perplexed by their own reality fearing the pessimistic possibilities of an uncertain future. In this scenario, dystopian narratives are not only related to tomorrow but are a warning for the present society. Based on Ursula K. Le Guin’s (2014) idea that science fiction works should be read as “thought-experiments”, this research covers how each audiovisual creations under study constructs its specific dystopian experiment and examine what is proposed by the set of cases as a dystopia from real society’s vision. In this study, for analysis, were selected three audiovisual productions: Fahrenheit 451 (1966), Movies Saga The Hunger Games (2012 - 2015) and the TV series Years and Years (2019). Evidentiary paradigm was used as methodology, basing it on Carlo Ginzburg (1989) and José Luiz Braga (2008) works. In each case, this research aimed to investigate and articulate clues and inferences that allowed us to learn the dystopia constructed not only at the narrative level, but as in the general structure of the object. During the comparison of the internal logics of each case, we searched for cross-sectional inferences that could reveal what they proposed as dystopia. At this level, it was possible to verify how dystopian experiments explores and potentialize aspects from reality and in that way can alert and stimulate reflection and social participation action in face of to the dark possibilities.
Keywords: Distopia; Experimento mental; Midiatização; Paradigma indiciário; Casos múltiplos; Dystopia; Thought-experiment; Mediatization; Evidentiary paradigm; Multiple cases; ACCNPQ::Ciências Sociais Aplicadas::Comunicação